Atomic Layer Deposition of Antibacterial Nanocoatings: A Review - Denis Nazarov; Lada Kozlova; Elizaveta Rogacheva; Ludmila Kraeva; Maxim Maximov (MDPI AG, 2023)
In recent years, antibacterial coatings have become an important approach in the global fight against bacterial pathogens. Developments in materials science, chemistry, and biochemistry have led to a plethora of materials and chemical compounds that have the potential to create antibacterial coatings. However, insufficient attention has been paid to the analysis of the techniques and technologies used to apply these coatings. Among the various inorganic coating techniques, atomic layer deposition (ALD) is worthy of note. It enables the successful synthesis of high-purity inorganic nanocoatings on surfaces of complex shape and topography, while also providing precise control over their thickness and composition. ALD has various industrial applications, but its practical application in medicine is still limited. In recent years, a considerable number of papers have been published on the proposed use of thin films and coatings produced via ALD in medicine, notably those with antibacterial properties. The aim of this paper is to carefully evaluate and analyze the relevant literature on this topic. Simple oxide coatings, including TiO2, ZnO, Fe2O3, MgO, and ZrO2, were examined, as well as coatings containing metal nanoparticles such as Ag, Cu, Pt, and Au, and mixed systems such as TiO2-ZnO, TiO2-ZrO2, ZnO-Al2O3, TiO2-Ag, and ZnO-Ag. Through comparative analysis, we have been able to draw conclusions on the effectiveness of various antibacterial coatings of different compositions, including key characteristics such as thickness, morphology, and crystal structure. The use of ALD in the development of antibacterial coatings for various applications was analyzed. Furthermore, assumptions were made about the most promising areas of development. The final section provides a comparison of different coatings, as well as the advantages, disadvantages, and prospects of using ALD for the industrial production of antibacterial coatings.